Development of a novel market forecasting tool and its application to hydrogen energy production in Scotland - Houghton, Tom; Cruden, A. (Elsevier Ltd, 2010)
The authors propose a novel model for forecasting the deployment of hydrogen energy systems based on a company value maximisation algorithm, designed to assist governments and other industry players in decision-making and the development of appropriate policy instruments. Current cost-minimisation approaches, such as MARKAL, have limitations particularly where price arbitrage between energy streams exists. A theoretical relationship between market sector valuations and investment activity is developed and the model is subsequently applied to the Scottish hydrogen energy market. Through the utilisation of net present value, revenue and profitability based valuations, the impact of investing in hydrogen energy infrastructure projects on three key market competitors is considered. It is shown that the three methods for calculating the value impact render different results suggesting that the use of a single method to assess forecast development scenarios, whether cost or value-based methods, may be misleading and that the holistic approach proposed is more realistic. The archivable value of this paper is to demonstrate the impact that investor expectations can have on investment decisions, a facet not captured in traditional methods of forecasting.